2003
DOI: 10.1037/h0100119
|View full text |Cite
|
Sign up to set email alerts
|

Covert sensitization: A generalization analysis in the laboratory and natural environment through the use of a portable-penile plethysmograph.

Abstract: Covert sensitization has been the most widely used behavioral treatment procedure to decrease deviant sexual arousal in sex offender therapy. However, it is unknown whether reductions of deviant sexual arousal in the laboratory generalize to the natural environment. This study conducted a generalization analysis of covert sensitization treatment effects to the natural environment using a portable-penile plethysmograph for a sex offender. Results indicated that deviant sexual arousal was reduced in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This study sheds light on the potential processes that may account for the reported lack of generalization of sexual offender treatment behaviors from the clinic to the community and other extratherapeutic settings (Marques et al, 2005; Rea et al, 2003; Rosen & Kopel, 1977). Marques et al (2005) reported some reoffenders indicated that they never implemented their relapse-prevention behaviors in the community, while Rea and his colleagues (2003) reported the lack of generalized conditioning from the laboratory to the natural environment. Although we did not evaluate reoffending in this study, we did examine a number of putative proximal measures to reoffending (O’Donohue & Letourneau, 1992).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This study sheds light on the potential processes that may account for the reported lack of generalization of sexual offender treatment behaviors from the clinic to the community and other extratherapeutic settings (Marques et al, 2005; Rea et al, 2003; Rosen & Kopel, 1977). Marques et al (2005) reported some reoffenders indicated that they never implemented their relapse-prevention behaviors in the community, while Rea and his colleagues (2003) reported the lack of generalized conditioning from the laboratory to the natural environment. Although we did not evaluate reoffending in this study, we did examine a number of putative proximal measures to reoffending (O’Donohue & Letourneau, 1992).…”
Section: Discussionmentioning
confidence: 90%
“…The participants' 100% compliance during the return to the follow-up TS probe verified the level of familiarity effect and suggested that the reduced levels of compliance during the NTS and CA probes were not due to mere temporal degradation. This study sheds light on the potential processes that may account for the reported lack of generalization of sexual offender treatment behaviors from the clinic to the community and other extratherapeutic settings (Marques et al, 2005;Rea et al, 2003;Rosen & Kopel, 1977). Marques et al (2005) reported some reoffenders indicated that they never implemented their relapse-prevention behaviors in the community, while Rea and his colleagues (2003) reported the lack of generalized conditioning from the laboratory to the natural environment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations